Establishment of a Novel Mouse Model for Atherosclerotic Vulnerable Plaque - Wang, Xueyu; Fu, Yahong; Xie, Zulong; Cao, Muhua; Qu, Wenbo; Xi, Xiangwen; Zhong, Shan; Piao, Minghui; Peng, Xiang; Jia, Ying; Meng, Lingbo; Tian, Jinwei (Frontiers in Cardiovascular Medicine, 2021)
Background and aims: Acute coronary syndrome (ACS) is a group of clinical syndromes characterized by rupture or erosion of atherosclerotic unstable plaques. Effective intervention for vulnerable plaques (VP) is of great significance to reduce adverse cardiovascular events. Methods: Fbn1C1039G+/- mice were crossbred with LDLR−/− mice to obtain a novel model for atherosclerotic VP. After fed with a high-fat diet (HFD) for 12 or 24 weeks, several diﬀerent pathological staining and immunohistochemistry were employed to evaluate the atherosclerotic lesion. Results: Compared to control mice, Fbn1C1039G+/-LDLR−/− mice developed more severe atherosclerotic lesions, the positive area of Oil Red O staining in aortic sinus were significantly increased after 12 weeks (21.7±2.0 vs 6.3±2.1) and 24 weeks (32.6±2.5 vs 18.7±2.6), respectively. More vulnerable plaque characteristics, significantly larger necrotic core (280±19 vs 105±7), thinner fiber cap (14.0±2.8 vs 32.6±2.7), apparent elastin fibers fragmentation and vessel dilation (3010±67 vs 1465±49), 2-fold augment of macrophages (8.5±1.0 vs 5.0±0.6)，obviously decreased smooth muscle cell (0.6±0.1 vs 2.1±0.2)and about 25% decrease in total collagen (33.6±0.3 vs 44.9±9.1) were observed in Fbn1C1039G+/-LDLR−/− compared to the control after 24 weeks. Furthermore, spontaneous plaque rupture, neovascularization, and intraplaque hemorrhage were detected in the model mice plaque regions instead of the control mice. Conclusions: Plaques in Fbn1C1039G+/-LDLR−/− mice fed on HFD show many features of human advanced atherosclerotic unstable plaques. These results suggest that Fbn1C1039G+/-LDLR−/− is a novel model for investigating the pathological and physiological mechanisms of advanced atherosclerotic unstable plaques.